Optimizing Economic Development For The Poor And Stunting In Soppeng Regency, South Sulawesi - Hasanuddin, Arnas; Hasanuddin, Achmad Anzhari; Risman, Risman (Jurnal Economic Resource, 2025)
This study aims to analyze the relationship between economic growth, poverty, and stunting in Soppeng Regency, South Sulawesi Province, and to identify factors that influence the effectiveness of economic development in reducing poverty and stunting rates. The research approach uses qualitative and quantitative methods with data collection techniques through surveys, in-depth interviews, and Focus Group Discussions (FGD) involving the poor, health workers, and policy makers. The results show that economic growth in Soppeng Regency during the 2016–2025 period has a negative correlation with poverty levels, with an average decrease of 0.57% per year. However, income inequality (Gini Ratio) has actually increased from 0.32 to 0.41, indicating that the benefits of growth have not been distributed evenly. In addition, the stunting rate remains high at around 30%, influenced by low access to nutritious food, health services, and the level of public knowledge about nutrition. These findings confirm that economic development in Soppeng is not yet fully pro-poor and pro-human development. Therefore, more inclusive policies are needed through improved access to infrastructure, strengthened integrated nutrition programs, and sustainable local economic development to reduce poverty and the prevalence of stunting.